2023
DOI: 10.1515/jbcpp-2022-0196
|View full text |Cite
|
Sign up to set email alerts
|

Single 30 min treadmill exercise session suppresses the production of pro-inflammatory cytokines and oxidative stress in obese female adolescents

Abstract: Objectives Regular treadmill exercise may result in changes in pro-inflammatory cytokines and oxidative stress. However, the way acute treadmill exercise mechanisms affect the changes in pro-inflammatory cytokines and oxidative stress in obese has not been comprehensively exposed. This study aimed to analyze the pro-inflammatory cytokines and oxidative stress between 30 min before treadmill exercise and 24 h after treadmill exercise in obese adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Body composition was measured during the pre-test and post-test using the TANITA Body Composition Analyzer DC3607601(2)-1604 FA (TANITA Corporation of America, Inc., Arlington Heights, IL, USA) (Pranoto et al, 2023). The data collected was body fat percentage (PBF), fat mass and muscle mass and BMI.…”
Section: Body Composition Assessmentmentioning
confidence: 99%
“…Body composition was measured during the pre-test and post-test using the TANITA Body Composition Analyzer DC3607601(2)-1604 FA (TANITA Corporation of America, Inc., Arlington Heights, IL, USA) (Pranoto et al, 2023). The data collected was body fat percentage (PBF), fat mass and muscle mass and BMI.…”
Section: Body Composition Assessmentmentioning
confidence: 99%
“…Numerous studies have indicated that physical exercise can lead to an elevation in Malondialdehyde (MDA) levels, serving as a marker of oxidative stress (Diaba-Nuhoho et al, 2018;Park & Kwak, 2016;Bhutia et al, 2011). Conversely, other studies demonstrate a notable decrease in MDA levels following exercise (Pranoto et al, 2023;Wang et al, 2023;Lu et al, 2021b), thereby confirming the existing ambiguity surrounding this issue, potentially due to the complexity of adaptive mechanisms during physical exercise. Consequently, this study seeks to validate the impact of moderate-intensity endurance training and strength training on the reduction of oxidative stress in students with obesity.…”
Section: Introductionmentioning
confidence: 98%
“…However, the results of a study by Salamat et al (2016) reported that moderateintensity treadmill exercise decreased IL-6 levels. Research by Pranoto et al (2023b) reported that IL-6 levels decreased after 24 hours of moderate-intensity treadmill exercise in obese women. However, the effect of exercise models in obesity on irisin and IL-6 parameters has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is considered one of the effective and efficient methods to prevent the increasing prevalence of obesity (Rejeki et al, 2021;Pranoto et al, 2023b;Merawati et al, 2023), through the mediation of irisin in the process of increasing energy expenditure, glucose, and lipid metabolism (Perakakis et al, 2017). The increase in irisin levels during exercise is a result of increased muscle contraction, which activates peroxisome proliferatoractivated receptor gamma coactivator-1-alpha (PGC1-α) to stimulate fibronectin type III domain-containing protein 5 (FNDC5) secretion and proteolytic cleavage of FNDC-5 membrane protein in skeletal muscle, resulting in the release of irisin into the bloodstream (Costello et al, 2018;Rejeki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%